Effects of Turkish Accounting Standards Application on Independent Audit Procedures - Fatih Coşkun Ertaş; Atila Karkacıer (Journal of Accounting and Management Information Systems (JAMIS), 2016)
The main purpose of this study is to determine the effects of Turkish Accounting Standards, which are compatible with International Financial Reporting Standards composed by the International Accounting Standards Board and providing to eliminate the differences among the accounting practices of the countries and to compare companies' accounting information, on independent audit procedures. Independent audits are essential to verify the accuracy and reliability of the financial statements belonging to companies. In this study, first of all, a number of examinations on the Turkish Accounting Standards applications have been carried out. Then, the information about the independent audits have been submitted. Finally, whether Turkish Accounting Standards Applications have positive or negative effects on independent audit firms and on independent auditors was searched through the questionnaire technique conducted among the independent auditing firms affiliated to the Free Market Board. Ultimately, it was concluded that the auditors consider International Accounting Standards as modern, reliable and sufficient to answer the purpose. In addition to this, Turkish Accounting Standards must be absolutely performed by companies, but it makes audit procedures difficult for audit firms and for independent auditors.
Keywords: M41; M42; 650; International Accounting Standards Board; Turkish Accounting Standards; Independent Audit